Quality of life among caregivers of children with autism spectrum disorder: A systematic review and meta-analysis - Taushanova, Maiya; Yermukhanova, Lyudmila; Kuanyshbekova, Marzhan; Sultanbayeva, Zhansaya; Tazhiyeva, Aigul; Musabayeva, Assem; Karibayeva, Indira (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Autism spectrum disorder (ASD) imposes substantial caregiving demands, often diminishing parental quality of life (QoL). This systematic review and meta-analysis aimed to quantify parental QoL using the WHOQoL-BREF, compare outcomes by caregiver subgroup (mothers, fathers, both parents) and identify domain-specific patterns. Methods: According to PRISMA guidelines, systematic searches in PubMed, Scopus, Web of Science, ScienceDirect and Google Scholar included cross-sectional and case–control studies using WHOQoL-BREF. Pooled means were calculated for each domain and overall QoL, with heterogeneity assessment and sensitivity analysis. Results: Our analysis revealed an overall mean QoL score of 41.59. The analysis also showed a consistent and significant gradient in parental QoL based on caregiving arrangements. Parents sharing childcare responsibilities reported a markedly superior overall QoL (mean score: 52.51) compared to those in father-led (29.75) or mother-led (27.56) arrangements. This hierarchical pattern, in which dual-parent caregiving was associated with the highest well-being, followed by father-led and then mother-led care, was consistently observed across all four domains of quality of life. The most pronounced disparities were identified within the social and environmental domains (total domain scores of 36.43 and 36.59, respectively), suggesting these areas are particularly sensitive to the caregiving model. Conclusions: Parents of children with ASD experience reduced QoL, especially in social and environmental domains. The key finding indicates that shared caregiving is a strong correlate of optimal parental QoL. Mothers are disproportionately affected, while shared caregiving appears protective. These findings support family-centered interventions and policies promoting caregiver well-being.